Decompression without Fusion for Lumbar Spinal Stenosis at a Single Mobile Segment in Adults with Ankylosing Spondylitis: A Report of 2 Cases. Issue 3 (12th July 2022) - Netsanet, Rahwa; Look, Nicole; Koshak, Christina; Patel, Vikas
Abstract : Case: This report details the cases of 2 older male patients with ankylosing spondylitis (AS) who presented with lumbar spinal stenosis at a single residual mobile segment and were treated with decompression without fusion. Both patients presented with severe symptoms in their lower limbs and opted to proceed with surgery. Conclusion: With autofusion above and below their single, stable mobile segment, decompression without fusion was a safe and effective procedure. A Coflex device was implanted in 1 patient. After successful surgery, both patients experienced significantly decreased symptoms.